Penerapan Teknologi Blockchain untuk Meningkatkan Keamanan dan Privasi Rekam Data Medis Pasien di Puskesmas Kampus Palembang - Mirza, A. Haidar; Pratama, Reza Aditiya (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
Puskesmas Kampus Palembang still relies on a conventional medical record system, making it vulnerable to cyberattacks and delays in administrative processes, particularly BPJS claims. This study aims to design and implement a web-based medical record management system by applying blockchain technology to enhance patient data security, privacy, and interoperability. The research method employed Rapid Application Development (RAD) consisting of requirement planning, design, implementation, and testing phases. Functional testing using blackbox testing showed that the system operated as required, storing patient data in a MySQL database while generating SHA-256 hashes recorded in the Ethereum blockchain via smart contracts. This implementation ensures the integrity and validity of medical data while improving the efficiency of healthcare services at Puskesmas Kampus Palembang.